Advanced descriptors for long-range noncovalent interactions between SARS-CoV-2 spikes and polymer surfaces - De Luca, Giorgio; Petrosino, Francesco; Di Salvo, Javier Luque; Chakraborty, Sudip; Curcio, Stefano (Separation and purification technology, 2022)
•Noncovalent long-range interactions between SARS-CoV-2 spike and polymer surfaces.•Polypropylene, Polyethylene Terephthalate, Polylactic Acid surfaces prepared by MD.•Molecular Mechanics simulations to define energy potential fields as descriptors.•Interactions follow the order PP ∼ PLA > PET and PLA > PP > PET for closed and open states.•Computed long-range interactions weaker than covalent or ionic bond energies. The recent pandemic triggered numerous societal efforts aimed to control and limit the spread of SARS-CoV-2. One of these aspects is related on how the virion interacts with inanimate surfaces, which might be the source of secondary infection. Although recent works address the adsorption of the spike protein on surfaces, there is no information concerning the long-range interactions between spike and surfaces, experimented by the virion when is dispersed in the droplet before its possible adsorption. Some descriptors, namely the interaction potentials per single protein and global potentials, were calculated in this work. These descriptors, evaluated for the closed and open states of the spike protein, are correlated to the long-range noncovalent interactions between the SARS-CoV-2 spikes and polymeric surfaces. They are associated with the surface's affinity towards SARS-CoV-2 dispersed in respiratory droplets or water solutions. Molecular-Dynamics simulations were performed to model the surface of three synthetic polymeric materials: Polypropylene (PP), Polyethylene Terephthalate (PET), and Polylactic Acid (PLA), used in Molecular Mechanics simulations to define the above potentials. The descriptors show a similar trend for the three surfaces, highlighting a greater affinity towards the spikes of PP and PLA over PET. For closed and open structures, the long-range interactions with the surfaces decreased in the following order PP ∼ PLA > PET and PLA > PP > PET, respectively. Thus, PLA and PP interact with the virion quite distant from these surfaces to a greater extent concerning the PET surface, however, the differences among the considered surfaces were small. The global potentials show that the long-range interactions are weak compared to classic binding energy of covalent or ionic bonds. The proposed descriptors are useful most of all for a comparative study aimed at quickly preliminary screening of polymeric surfaces. The obtained results should be validated by more accurate method which will be subject of a subsequent work.